Evaluation of NOx emissions characteristics in a CO2-Free micro-power system by implementing a perforated plate. (July 2021) - Cai, Tao; Zhao, Dan; Sun, Yuze; Ni, Siliang; Li, Weixuan; Guan, Di; Wang, Bing
Abstract: Ammonia (NH3 ), as a carbon-free fuel with a high hydrogen content, has been considered as a promising candidate to be applied for transportation, propulsion, and power generation sectors. However, due to the presence of nitrogen atoms, direct combustion of NH3 features a high NO x emission, which could hinder its wide application. Thus it is important to mitigate or minimize these emissions. For this, a three-dimensional (3D) computational model is developed by considering a detailed chemical-kinetic mechanism. The effects of 1) the perforated plate porosity σ, 2) the perforated plate thickness t 1, 3) the perforated orifice off-z axis distance d, and 4) inlet thermodynamic pressure P in are evaluated. Numerical results indicate that σ plays an important role in determining the NO formation. This is the combined effect of the strong species preferential diffusion and low flame temperature within the recirculation zone. Furthermore, varying t 1 is shown to affect the NO generation rate due to the varied recirculation zone. Although the flow field is affected by d to some degree, it has a negligible effect on the NO generation. Finally, the emission behavior is found to have a strong dependence on P in . Approximately 50% reduction of NO emission is achieved as the inlet pressure is varied from 1 to 3 atm. The present work opens up an applicable way to enable low-NO x ammonia-fueled power systems, and some of the findings could be applied for hydrocarbon systems design. Highlights: A perforated plate-implemented micro-combustor is numerically simulated. Effects of perforated plate parameters on the NO x performance are evaluated. Elevating the inlet pressure significantly reduces the NO formation. A low-NO x NH3 -fueled combustor is achievable.